STIMULASI PERTUMBUHAN VEGETATIF PHALAENOPSIS DENGAN INDOLE ACETIC ACID (IAA) - Astutik Astutik; Ricky Indri Hapsari (Universitas Tribhuwana Tunggadewi, 2009)
The objectives of this research was leaning and finding the consentrade of IAA (Indole Acetic Acid) on vegetative growth of Phalaenopsis sp. The research used a randomly completely block design consisting of five treatments on level IAA consentration : 0 mg/l (A0), 100 mg/l (A1), 200 mg/l (A2), 300 mg/l (A3) and 400 mg/l (A4). Every treatment was replicated five times. The observed parameters included the amount of increasing leaves, the length and width of lives, the amount of increasing roots and the length of increasing roots. The results showed that the consentrade 400 mg/l IAA was the most appropriate consentrade to stimulated on vegetative growth of Phalaenopsis sp. The length of increasing leaves was 0,93 cm and the amount of increasing roots was 3,90